Facial Plastic Surgery on Instagram: What Is Trending? What Is Working?. (18th December 2020) - Basa, Krystyne; Spiegel, Jeffrey H
Abstract: Background: Instagram has become a prominent way for facial plastic surgeons to advertise their work and communicate with patients. Some providers develop globally popular profiles, becoming "influencers" in their field. Objectives: We sought to characterize posts found on top profiles by type and determine the degree of patient interaction within each type. Methods: A social media tracking tool (Awario, Belarus) compiled a list of the top 33 facial plastic surgery Instagram profiles based on number of followers and "reach, " obtained on September 22, 2019. Profiles not belonging to American Board of Facial Plastic and Reconstructive Surgery (ABFPRS)-certified surgeons were excluded, leading to 20 profiles. The most recent 18 posts at the time of data extraction were categorized into: (1) clinical or professional, (2) lifestyle, and (3) patients. The average number of "likes, " as a percentage of total followers, was calculated for each category for each profile. Data were gathered from September to November 2019. Results: Most top profiles belong to ABFPRS-certified surgeons and were not verified. Clinical pictures and patient posts were 42.78% and 41.94% of those sampled, respectively. Lifestyle content was 19.05%. Followers interacted with clinical posts the most, having an average of 6.79% of follower interaction. Patient and lifestyle posts had 2.88% and 3.81%, respectively. Conclusions: Instagram is an important communication tool for facial plastic surgeons to engage in promotion and education. It is important to understand what trends tend to attract followers and engagement. Our study showed that more clinical content, separate from patient pictures, tended to be popular with both providers and followers.